2021
DOI: 10.1002/smll.202101133
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Improvement of Efficiency and Stability of Organic Photovoltaic Cells by using a Cross‐Linkable Fullerene Derivative

Abstract: Improving power conversion efficiencies (PCEs) and stability are two main tasks for organic photovoltaic (OPV) cells. In the past few years, although the PCE of the OPV cells has been considerably improved, the research on device stability is limited. Herein, a cross‐linkable material, cross‐linked [6,6]‐phenyl‐C61‐butyric styryl dendron ester (c‐PCBSD), is applied as an interfacial modification layer on the surface of zinc oxide and as the third component into the PBDB‐TF:Y6‐based OPV cells to enhance photovo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 51 publications
1
34
0
1
Order By: Relevance
“…The commonly used crosslinking units include bromine, vinyl, acrylate, azide, and oxetane groups, which can be activated upon UV‐light exposure or thermal annealing. [ 34,35 ] For example, Fréchet et al. developed the photo‐crosslinkable bromine‐functionalized copolymer P3HT‐Br/PCBM blend to improve the thermal stability of OSCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly used crosslinking units include bromine, vinyl, acrylate, azide, and oxetane groups, which can be activated upon UV‐light exposure or thermal annealing. [ 34,35 ] For example, Fréchet et al. developed the photo‐crosslinkable bromine‐functionalized copolymer P3HT‐Br/PCBM blend to improve the thermal stability of OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used crosslinking units include bromine, vinyl, acrylate, azide, and oxetane groups, which can be activated upon UV-light exposure or thermal annealing. [34,35] For example, Fréchet et al developed the photo-crosslinkable bromine-functionalized copoly mer P3HT-Br/PCBM blend to improve the thermal stability of OSCs. [36] Hsu and co-workers revealed that the crosslinked fullerene derivatives of [6,6]-phenyl-C61-butyric styryl dendron ester (PCBSD) preserve the blend film morphology and increase device stability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Hou and co-workers employed c-PCBSD as the third component of the PBDB-TF : Y6-based OPV cells to enhance the long-term stability. 192 Finally, device C maintained 90% of its initial PCE under 100 °C thermal treatment for 500 h, which greatly improved device stability (Fig. 16d).…”
Section: Crosslinkable Active Layer Materialsmentioning
confidence: 93%
“…15). [188][189][190][191][192] For example, Li and co-workers introduced highly reactive acrylate groups into fullerenes to synthesize PC 61 BA with a similar molecular structure and molecular volume to PC 61 BM. 188 They used PC 61 BA as the acceptor and P3HT as the donor to fabricate the OPV device, which is similar to the efficiency of the reference device with PC 6l BM as the acceptor.…”
Section: Crosslinkable Active Layer Materials In Opvsmentioning
confidence: 99%
“…">IntroductionReproducibility in time and space is one of the major concerns for organic electronics. [1][2][3][4][5] To wit, researchers attempted to fabricate large-area organic modules with obtaining desirable device performance after cycling operations as much as…”
mentioning
confidence: 99%